The guns of Navarone [videorecording (DVD)] - Tiomkin, Dimitri, 1894-1979 (Columbia classics., 2007)
A British-American epic adventure war film inspired by the Battle of Leros during the Dodecanese Campaign of World War II in which a commando team of Allied military specialists are recruited for a dangerous but imperative mission to infiltrate a Nazi-occupied fortress and disable two long-range field guns so that 2,000 trapped British soldiers may be rescued. Faced with an unforgiving sea voyage, hazardous terrain, and the possibility of a traitor in their midst, the team must overcome the impossible without losing their own lives.